Molecular screening with liquid biopsy for anti-EGFR retreatment in metastatic colorectal cancer: preliminary data from the randomized phase 2 PARERE trial - Germani, Marco Maria; Vetere, Guglielmo; Giordano, Mirella; Ciracì, Paolo; Capone, Iolanda; Tamborini, Elena; Conca, Elena; Busico, Adele; Pietrantonio, Filippo; Piva, Vittoria Matilde; Boccaccino, Alessandra; Simionato, Francesca; et al. (Frontiers in Oncology, 2024)
Retreatment with anti-EGFR monoclonal antibodies is a promising strategy in patients with RAS/BRAF wild-type (wt) metastatic colorectal cancer (mCRC) who achieved benefit from previous anti-EGFR exposure, upon exclusion of mutations in RAS/BRAF genes according to circulating tumour DNA (ctDNA) analysis by means of liquid biopsy (LB). This treatment approach is now being investigated in the randomized phase II trial PARERE (NCT04787341). We here present preliminary findings of molecular screening.Patients with RAS/BRAFV600E wt mCRC according to tissue genotyping who benefited from previous anti-EGFR based treatment and then experienced disease progression to EGFR targeting, fluoropyrimidines, oxaliplatin, irinotecan and antiangiogenics, were eligible for screening in the PARERE trial. The next generation sequencing (NGS) panel OncomineTM was employed for ctDNA testing.218 patients underwent LB and ctDNA sequencing was successfull in 201 of them (92%). RAS/BRAFV600E mutations were found in 68 (34%) patients and were mainly subclonal (median variant allele fraction [VAF] for KRAS, NRAS, BRAF mutant clones: 0.52%, 0.62%, 0.12%, p=0.01), with KRASQ61H being the most frequently detected (31%). Anti-EGFR free interval did not predict ctDNA molecular status (p=0.12). Among the 133 patients with RAS/BRAFV600E wt tumours according to LB, 40 (30%) harboured a mutation in at least another gene potentially implied in anti-EGFR resistance, mainly with subclonal expression (median VAF: 0.56%). In details, alterations in PIK3CA, FBXW7, GNAS, MAP2K, ERBB2, BRAF (class I and II non-BRAFV600E), SMAD, EGFR, AKT1 and CTNNB1 occurred in 13%, 8%, 7%, 3%, 2%, 2%, 1%, 1%, 1% and 1% cases, respectively. Co-mutations were detected in 13 (33%) out of 40 of patients.This is the largest prospective cohort of mCRC patients screened with LB for anti-EGFR retreatment in a randomized study. ctDNA genotyping reveals that at least one out of three patients candidate to retreatment should be actually excluded from this therapy, and other potential drivers of anti-EGFR resistance are found in about one out of three patients with RAS/BRAFV600E wt ctDNA.